Bacteriological aspects of Darier's disease. (19th October 2012) - Dodiuk‐Gad, R.; Cohen‐Barak, E.; Ziv, M.; Shani‐Adir, A.; Shalev, S.; Chazan, B.; Raz, R.; Colodner, R.; Amichai, B.; Zlotogorski, A.; Keness, Y.; Rozenman, D.
Abstract Background There are no established data on the prevalence of bacterial colonization of lesional skin, nares and perineum in Darier's disease (DD), or its contribution to the clinical manifestations of the disease. Objective To determine the prevalence of bacterial colonization of lesional skin and Staphylococcus aureus (S. aureus) in nares and perineum in 75 patients with DD, the association of these parameters with disease and patient characteristics, and the features of the bacterial skin infection in this group. Methods Medical interviews and physical examinations were performed. Bacteria were isolated from swabs taken from lesional skin, nares and perineum. Results S. aureus was isolated in 68%, 47% and 22% of lesional skin, nares and perineum cultures respectively. Subjects with positive S. aureus culture from lesional skin and/or nares had a statistically significant higher percentage of skin area affected and a more severe disease than patients with negative culture. Thirty of the 75 patients (40%) recalled bacterial skin infection, most often on the chest. Conclusions Patients with DD have high prevalence of S. aureus colonization in lesional skin and nares, with a correlation between disease severity and extent of the colonization. Further studies examining the consequences of S. aureus eradication in those sites may establish the need for S. aureus lesional skin and nares colonization screening and eradication as part of the treatment of DD exacerbations.